Reflux esophagitis in children with feeding problems: A preliminary study - Lia Mulyani; Badriul Hegar; Alan R. Tumbelaka; Ening Krisnuhoni (Indonesian Pediatric Society, 2010)
Background Untreated gastroesophageal reflux can cause reflux esophagitis, a condition characterized by damage to the esophageal mucous layer due to exposure to caustic gastric contents. Manifestation of esophagitis in young children include feedingproblems, irritability, and backô€€³arching. Persistent esophagitis may cause growth failure, gastric bleeding, and anemia. Reflux esophagitis should be considered an etiology of feeding problems, especially in children with a history of gastroesophageal reflux during infancy.Objective The purpose of this study is to detennine the prevalence of reflux esophagitis in children with feeding problems.Methods A cros-sectional study was done in November 2007 to April 2008. Children under 5 years of age with feeding problems and a history of regurgitation or vomiting started from age 6 months or more underwent endoscopy and biopsy examinations. Reflux esophagitis was diagnosed based on the Los Angeles classification of endoscopic examination.Results Reflux esophagitis was diagnosed in 18 of 21 children with feeding problems and a history of regurgitation or vomiting. Most subjects were boys aged 12 to36 months. Feeding problems has lasted for more than 6 months, regurgitation or vomitingfor more than 12 months, and suffered from mild malnutrition. Vomiting was observed to be a common symptom in children with reflux esophagitis.Conclusion The prevalence of reflux esophagitis in children with feeding problems and a history of regurgitation or vomiting started from age â‰¥ 6 months is high, therefore it will influence treatment.